Post-COVID spirometric abnormalities in workers with intermittent high-altitude exposure: A cross-sectional study in Peru - Jair Alonso Góngora-Bendezú; Marleyssi Valeria Martinez-López; Angel David Aguinaga-Fernandez; Marlon Yovera-Aldana (PLoS ONE, 2026)
Introduction Persistent pulmonary sequelae after SARS-CoV-2 infection remain a concern in workers exposed to environmental and physiological stressors such as intermittent high-altitude hypoxia. Few studies include pre-pandemic spirometry or focus on this occupational group. Methods A cross-sectional study was conducted in 400 sea-level-born workers intermittently exposed to altitudes >2500 m, all with confirmed COVID-19. Only A/B-quality spirometry from 2024 was included. Sociodemographic, clinical, and occupational variables were assessed, and adjusted prevalence ratios (aPR) were estimated using Poisson regression with robust variance. Results Overall, 72.2% of workers showed spirometric abnormalities (40.5% mixed, 20.8% restrictive, 11.0% obstructive). Independent predictors included obesity (aPR 1.35; 95% CI 1.19–1.53), higher Charlson index (aPR 1.49; 95% CI 1.33–1.68), ≥ 5 years of inhalant exposure (aPR 1.64; 95% CI 1.43–1.89), ≥ 7 years of intermittent high-altitude exposure (aPR 1.81; 95% CI 1.60–2.05), and severe COVID-19 (aPR 1.65; 95% CI 1.41–1.91). Conclusions Over 70% of participants showed abnormal spirometry was found in post-COVID-19 workers with intermittent high-altitude exposure. Respiratory function monitoring should be reinforced in this occupational group, especially among those with higher clinical and environmental risk factors.